Mediating role of work-related attitudes between leadership styles and well-being - Ghulam Abbas; Muhammad Tahir Khalily; Muhammad Naveed Riaz (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
The main purpose of the study is to examine the mediating role of work-related attitudes between two leadership styles and well-being of university teachers. The work-related attitudes included job satisfaction, organizational commitment, turnover intention and innovative work behavior. It is a survey based research in which cross-sectional design has been used. Thus data were collected using Multifactor Leadership Questionnaire, Job Satisfaction Scale, Organizational Commitment Scale, Turnover Intention Scale, Innovative Work Behavior Scale and Warwick-Edinburg Mental Well-Being Scale. Participants comprised of 756 teachers (including 156 Head of Departments and 600 teachers). Hierarchical regression analysis confirmed that work-related attitudes partially mediated between leadership styles and well-being of teachers. The study explained that supervisors in the educational institutions directly influence the job of the subordinates and job related attitudes of subordinates affect their well-being.
Keywords: 330; leadership styles; work related attitudes; well-being